(untitled) (Journal of Forest and Livelihood, 2024)
Nepal hosts a wide range of NTFPs and bio-diversity including over 700 species of medicinal herbs. NTFPs are an important part of the Nepalese economy, both locally as well as nationally. Recent studies indicate that several commercially valuable species are being over used and degraded (Edward 1996; Malla et al. 1995; Hertog 1995; Karki 1996; Sharma, 1996) due to higher demand as raw materials for herbal industries in India and other countries. As a result of pre-mature harvesting, over-exploitation and haphazard collection of NTFPs, the productive potential of the whole forest ecosystem is undermined. The damage is particularly serious in terms of pressure on the few species identified for trade, as well as pre-mature harvesting, physical damage, and haphazard collection. This indicates a need to assess the reasons behind unsustainable practices, and identify options for sustainable management. Based on the recently collected field data from the western Himalayan region (Humla and Dolpa districts), the paper analyzes dynamics of unsustainable harvesting and management practices of NTFPs, with particular reference to Jatamansi (Nardostachysgrandiflora), Kutki (Picmrhiza scrophulariiflora) and Sugandhawal (Valeriana jatainansi). Key variables within institutional, economic, natural/physical, and policy aspects are considered for analysis. Finally, potential actions that can be taken to improve harvesting practices are also suggested.